2017
DOI: 10.21873/anticanres.11532
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Anti-apoptotic Protein BAG3 in Human Sebaceous Gland Carcinoma of the Eyelid

Abstract: Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It has been reported that BAG3 is highly expressed in many kinds of primary tumors, including ovarian cancer, and glioblastoma [ 10 13 ]. In addition, BAG3 is able to modulate some tumor biology processes, involving cell apoptosis, growth, cytoskeleton organization, and differentiation [ 14 , 15 ]. Some studies have reported that the overexpression of BAG3 inhibits drug-induced or serum-deprivation apoptosis in some degree and the inhibition of BAG3 promotes tumor cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BAG3 is highly expressed in many kinds of primary tumors, including ovarian cancer, and glioblastoma [ 10 13 ]. In addition, BAG3 is able to modulate some tumor biology processes, involving cell apoptosis, growth, cytoskeleton organization, and differentiation [ 14 , 15 ]. Some studies have reported that the overexpression of BAG3 inhibits drug-induced or serum-deprivation apoptosis in some degree and the inhibition of BAG3 promotes tumor cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…BAG3 has been found to be upregulated during malignant cell transformation and is present in detectable amounts in pancreatic adenocarcinoma (PDAC), breast, lung, colorectal, ovarian and cervical cancers. Expression of BAG3 significantly effects the prognosis of cancer patients by hyper-activating cell-survival pathways, evading cell-death mechanisms and hindering the efficacy of commercially available chemotherapy and radiotherapy options (Basile et al, 2019;Chiappetta et al, 2012Chiappetta et al, , 2014Yunoki et al, 2017). This voracious nature of BAG3 is attributed to its multifaceted structure that allows it to play pivotal roles in cell pathways encompassing proliferation, metastasis, angiogenesis, autophagy, apoptosis and more.…”
Section: Procancerous Role Of Bag3mentioning
confidence: 99%
“…The molecular mechanisms underlying the pathogenesis and progression of SGC remain to be fully elucidated. As is the case with other cancers, most SGC have point mutations in the p53 tumor suppressor gene ( 15 ) and overexpressed anti-apoptotic proteins including X-linked inhibitor of apoptosis (XIAP) ( 16 ) and BAG cochaperone 3 (BAG3) ( 17 ). High expression of growth factor receptors such as vascular endothelial growth factor receptor-2, epidermal growth factor receptor, and platelet-derived growth factor receptor are also known as clinicopathologic features of SGC ( 18 ).…”
Section: Introductionmentioning
confidence: 99%